South African medical device regulatory pathways: A case study of the effect of the emergency authorization protocols during the Covid-19 pandemic - Etuket, Maureen (Department of Human Biology, 2024)
Local medical device translation in Low-and Middle-Income countries (LMICs) is unpredictable and accompanied by demanding, complex, and time-consuming regulatory processes. This complicates local innovation and manufacturing and further restricts access to safe, dependable, and appropriate medical devices (World Health Organisation, 2012). The Covid-19 pandemic accelerated medical technology advancement through the use of Emergency Use Authorisation (EUA) protocols. One such case, which used EUA protocols, is South Africa's National Ventilator Project (NVP). In this study, the NVP is presented as a case study to explore medical device regulations during the Covid-19 outbreak. Semi-structured interviews were held with eight significant NVP participants and this was the primary source of data for the case study. These participants were identified through documents and snowball sampling. The participant's employment history, NVP role and experience, and regulatory recommendations were discussed in the interviews. Interviews were transcribed and iteratively coded with NVivo software (QSR International Pty Ltd., 2020), resulting in three major themes: People, processes, and products in EUAs; the medical device regulatory space; and sustainability of the local medical device industry. Most participants credited the success of the NVP to the interdisciplinary project team. Some participants, from highly-regulated, but non- medical device industries, found the medical regulatory environment frustrating. All participants agreed that systems engineering (SE) methodologies must be implemented in the regulatory space. During the NVP, adapting SE enabled the coordination and facilitated the integration of multiple stakeholder's needs from ideation, through translation to commercialisation and end-use of the device. Additionally, ensuring the sustainability of local innovation through preferential procurement was emphasised. In the contexts of South Africa and Africa, the case study's findings can be utilized to guide policy and provide long-term regulatory paths for medical devices.